2020
DOI: 10.1186/s12870-020-02537-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals ethylene-mediated defense responses to Fusarium oxysporum f. sp. cucumerinum infection in Cucumis sativus L.

Abstract: Background: Fusarium wilt, caused by Fusarium oxysporum f. sp. cucumerinum (Foc), is a severe disease affecting cucumber (Cucumis sativus L.) production worldwide, but mechanisms underlying Fusarium wilt resistance in cucumber remain unknown. To better understand of the defense mechanisms elicited in response to Foc inoculation, RNA sequencing-based transcriptomic profiling of responses of the Fusarium wilt-resistant cucumber line 'Rijiecheng' at 0, 24, 48, 96, and 192 h after Foc inoculation was performed. Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…In the study performed by Wang et al [22], strong expression of the PR4 gene was observed in response to fungus C. cassiicola in both resistant and susceptible lines. Other authors also pointed out activation of this gene in cucumber response to various pathogens [16,23,47].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the study performed by Wang et al [22], strong expression of the PR4 gene was observed in response to fungus C. cassiicola in both resistant and susceptible lines. Other authors also pointed out activation of this gene in cucumber response to various pathogens [16,23,47].…”
Section: Discussionmentioning
confidence: 91%
“…In cucumber, such an approach was applied to study response to viruses, including Cucurbit Chlorotic Yellows Virus (CCYV) and Cucumber Mosaic Virus (CMV) [17,18], oomycete pathogens Pseudoperonospora cubensis and Phytophthora melonis [19][20][21], and fungal pathogens like Botrytis cinerea, Corynespora cassiicola, Fusarium oxysporum f. sp. cucumerinum, Sphaerotheca fuliginea, and Alternaria cucumeriana [16,[22][23][24][25]. RNA-seq was also used to investigate cucumber response to aphid and spider-mite infestations [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Followed the inoculation phenotypes and sequencing verification, the Foc strain was confirmed and then cultured in potato dextrose broth in plates on a shaker (180 rpm) at 28 °C for 3 days. The concentration was adjusted to 10 6 spores/mL using sterile distilled water prior to the inoculation of 14-day large cucumber seedlings at second true-leaf stage via a published dip-inoculation method [ 22 ]. Three replicates of seedling roots were harvested at 0, 24, 48, 96, and 192 h after the Foc inoculation.…”
Section: Methodsmentioning
confidence: 99%
“…The Foc acted as a typical soil-borne and destructive fungal disease, which firstly infected the roots of cucumber growth process in field and induced the responsive genes to defense FW. We used the cucumber seedlings to inoculate with Foc using the dipinoculation method [6]. The Foc strain was propagated on potato dextrose agar (PDA) medium-containing plates at 28 • C for 4 d, then cultured in potato dextrose broth (PDB) medium on a shaker at 180 rpm at 28 • C for 3 d. The spore suspension was adjusted to 10ˆ6 spores/mL using sterile distilled water for inoculation of the cucumber seedlings.…”
Section: Plant Materials and Foc Inoculationmentioning
confidence: 99%
“…Cucumber Fusarium wilt (FW) is a typical soil-borne and destructive fungal disease caused by F.oxysporum f. sp. cucumerinum (Foc) [2], which severely restricts cucumber growth and yield [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%